Empowerment of Former Indonesian Migrant Workers (PMI) Through the Purnama Subang Program by PT Pertamina EP Subang Field - Luthfi, Wazirul; Mutrofin, Mutrofin; Putri, Ratnasari Utama; Hayati, Ashlihul (Altruism: The Indonesian Journal of Community Engagement, 2025)
Indonesian Post-Migrant Workers faces numerous challenges in the process of social and economic reintegration upon their return to their homeland. These challenges include low levels of education, financial difficulties, and limited access to business opportunities. In response to these issues, PT Pertamina EP Subang Field has initiated the Purnama Subang Program as a community-based empowerment initiative aimed at supporting returnee PMI. This program encompasses skills development, social entrepreneurship enhancement, waste management, and micro-business assistance. This study employs the Community-Based Participatory Research (CBPR) method to assess the effectiveness of the Purnama Subang Program in enhancing the well-being of returnee PMI. The findings indicate that the program has successfully improved participants' skills, financial literacy, and access to business opportunities, while also generating a significant positive impact on the local economy. An evaluation conducted through the Community Satisfaction Index (IKM) reveals a high satisfaction level of 88.50%, whereas the Social Return on Investment (SROI) assessment yields a value of 2.07, demonstrating that the program delivers social and economic benefits that exceed its costs.Accordingly, the Purnama Subang Program has the potential to serve as a sustainable empowerment model for returnee PMI in other regions.